Is there a Global South? A Perspective from South Asia. (March 2014) - Tripathi, Rahul
Much of the writings on the Global South in recent years have focused on the role that some of the emerging economies within the developing world might play in the unfolding global scenario. It is asserted that the rise of a group of middle-level players, given their economic and political profile in global affairs, may be critical in shaping future global outcomes. Such an influence may come at a time when the power of the established powers is seen in relative decline, particularly given the volatility of the global political economy in recent years. The article tries to revisit this assumption from a South Asian perspective and tries to explore the fundamentals of the Global South in terms of its ability to provide alternatives. Taking South Asia as a test case, the article argues that the term 'South' itself as a homogeneous entity is problematic from the point of view of characterisation as well as actualisation of the potential alternatives. While this does not rule out coalition building and collective action between countries sharing common interests and objectives, such coalition building may be more diffused and episodic rather than have the potential to provide 'alternative orders'.